PARTIAL MELT DISTRIBUTIONS FROM INVERSION OF RARE EARTH ELEMENT CONCENTRATIONS - McKenzie D.; O'Nions R.K. (My University, 1991)
Inverse theory is used to calculate the melt distribution required to produce the rare earth element concentrations in a wide variety of terrestrial and extra-terrestrial magmas. The concentrations of the major and minor elements in the source regions are assumed to be the same as those for the bulk Earth, and the peridotite mineralogy calculated from the mineral compositions by least squares. Rare earth element partition coefficients are then used for inversion, assuming the melt generation is by fractional melting. The mean composition of the magmas is taken to be an estimate of the average composition of the melt. For n-typc and e-type MORB the results agree well with the adiabatic decompression calculations if the potential temperatures are 1300 and 1500°C respectively. The major and minor element compositions calculated from the melt distribution obtained from the inversion also agree well with those observed. The observations are consistent with a melt fraction that increases monotonically towards the surface, starting at ∼ 80 km and producing ∼ 9 km of melt in the case of n-type MORB, and at ∼ 120 km to produce 23 km in the case of e-type MORB. The inversion calculations show that the melt fractions produced beneath an intact plate by a plume like that beneath Hawaii are smaller, and are also in agreement with the adiabatic calculations if the potential temperature of the plume is ∼ 1500°C. Much of the melt is produced in the depth and temperature range of the transition from garnet to spinel peridotite, in agreement with laboratory experiments and with the full convective models of the Hawaiian plume. The inversion calculations show that the source region for Hawaiian tholeiites changes with time from primitive to depleted mantle. This behaviour is likely to result from percolation, and the processes involved can be understood with the help of a simple analytic model. The last, post-erosional, magmas produced on Oahu come from a source that has been uniformly enriched in all rare earth elements by a factor of about two. Magmas associated with island arcs come from two sources. One resembles that of n-type MORB, and probably is produced by adiabatic upwelling. The other generates calc-alkaline basalt strongly enriched in light rare earth elements, but with a smaller constant enrichment between Gd and Lu. This composition is consistent with the extraction of a melt fraction of 1% from a source containing ∼9% of amphibole. Such a source region can also account for the low values of Ti and Nb, and perhaps also of Ta, observed in island arc magmas. Basaltic andesites and andesites from island arcs show the same amphibole signature, and can be produced from the calc-alkaline basalts by fractional crystallization if amphibole separates with olivine and orthopyroxene. The percolation of a small melt fraction through a mantle wedge that contains considerable amounts of amphibole can only transport very incompatible elements, such as He, U, Th, and Rb, towards the Earth's surface. Sr and Nd are likely to be too compatible to move against the matrix flow, but Pb may do so locally. These results have important implications for the isotopic systematics of the upper mantle. The melt distributions obtained from ophiolites are like those for island arc tholeiites, though a potential temperature of 1400 °C fits the results better than does one of 1300°C. Archaean tholeiites and basaltic komatiites give melt distributions similar to that of e-type MORB from Iceland, and can be produced by adiabatic decompression if the mantle potential temperature is 1500cC, with tholeiites having lost more material by fractional crystallization. The melt distribution obtained from komatiites requires the melt fraction to reach ∼60% at the surface. Though the calculated compositions agree with those observed, decompression is unable to generate such large melt fractions. Inversion shows that plateau basalts can be produced from the upper mantle beneath the plates by adiabatic upwelling beneath a mechanical boundary layer 60 km thick. Many of the varied alkali-rich continental magmas are generated by melting an enriched source in the stability field of garnet peridotite. The average enrichment required, by a factor of between two and five, can be produced by the addition of a small melt fraction. Carbonatites show no evidence of amphibole involvement at any stage, a result that is consistent with their formation by liquid immiscibility. Inversion of the rare earth element concentrations in shales gives a melt distribution similar to that from calc-alkaline basalts from island arcs, with a strong amphibole signature. Generation of the continental crust by separation of calc-alkaline magma from 40% of the mantle can account for the difference between primitive and depleted mantle. Low-K highland basalts from the Moon can be produced directly from the average primitive lunar mantle if the melt fraction involved is ~0-5%, and if they were generated in the stability field of plagioclase and spinel peridotite. Intermediate-K highland basalts come from a source that has been enriched by a factor of about two, and show no evidence of amphibole involvement. The rare earth concentrations in mare basalts require melt fractions of up to 7% in the spinel peridotite stability field, and can be generated by adiabatic upwelling of mantle whose potential temperature is 1300°C beneath a mechanical boundary layer that is 150 km thick. Because lunar gravity is only one-sixth of that of the Earth, the thickness of the melting zone and the volume of melt produced are six times greater for the Moon than for the Earth for the same value of Tp. Both low-Ti and high-Ti mare basalts may have lost as much as 70 and 85% respectively of their original material through crystal fractionation. It is, however, difficult to understand how such an origin can account for the high magnesium concentrations. Basaltic achondrites involve melt fractions of 10-15%, generated in the spinel or plagioclase stability field.
Keywords: Archaean; Precambrian::Archean; Докембрий::Архей